FRI0287 Assessment of anti-TNF therapies in patients with spondyloarthropaties: Gait analysis as alternative. (23rd January 2014) - Garrido-Castro, J.L.; Collantes, E.; Medina, R.; Galisteo, A.M.; Gonzalez, C.; Ruiz, D.; Font, P.; Gomariz, E.M.
Abstract : Background: Mobility measures have been used to demonstrate the effectiveness of anti-TNF therapies for the treatment of spondyloarthropathies (SpA) but they are not enough sensitive to change in short term. Gait Analysis is a noninvasive method used in certain clinical areas, although not very used in rheumatology. SpA produces stiffness in the back that leads to more cautious gait pattern. Anti-TNF therapies reduces inflammation and therefore improve patient's mobility. Objectives: To analyze kinematic gait changes in SpA patients produced by treatments based on anti-TNF. Methods: Gait Analysis on 15 patients diagnosed with SpA was evaluated using a motion capture system (UCOTrack). Tests were performed before receiving anti-TNF treatment (baseline), after 8 and 24 weeks. We analyzed spatio-temporal parameters such as cadence, % of support and speed. Ranges of motion in joints: trunk, pelvis, hip, knee and ankle were measured. BASMI, BASDAI, BASFI and ASQoL were also analyzed. Results: All joint motions were increased with coefficient of variation (CV) from 3.5% to 22.4%. Significant difference (p<0.05) appeared at 8 weeks in trunk flex/ext and in pelvic obliquity, and at 24 weeks in pelvic rotation and hip flex/ext. A significant improvement was detected in cadence and support at 8 weeks. There were reduction in outcome indexes varying from 0.14 in BASMI (7.3%) to 1.18 in ASQoL (22.6%), although this difference were not statistically significant. The figure shows range of movement recorded before treatment (dot lines) and 24 weeks after (solid lines). Conclusions: Improvements in pain and inflammation caused a higher cadence and lower support. No significant differences were found in knee and ankle, due to patients were in early stages of the disease. Main differences were detected in coordinating the movement of the pelvis. Responsiveness in conventional assessment methods was poor. Therapy improves the patient's walking ability. Gait Analysis may be an effective tool in assessing the effectiveness of these treatments. Disclosure of Interest: None Declared